1992
DOI: 10.1038/hdy.1992.19
|View full text |Cite
|
Sign up to set email alerts
|

On the developmental theory of ageing. II. The effect of developmental temperature on longevity in relation to adult body size in D. melanogaster

Abstract: Flies from a wild type strain of Drosophila melanogaster, previously kept at 25°C, were reared at either 20, 25 or 29°C. As expected, developmental time and adult body size decreased with increasing temperature. Adult longevity of flies reared at 25°C was slightly greater than that of flies raised at 20 or 29°C when measured at all three temperatures. This may reflect the laboratory history of the strain. On the whole, it appeared that longevity was independent of adult body size. These results support our pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
72
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 34 publications
12
72
1
Order By: Relevance
“…The actual causes of gene-by-environment interactions remain unknown for most characters, but may reflect significant changes in the underlying physiology and genetic determination of the affected traits. Lifespan appears to be a suitable trait for the study of such interactions, since it is assumed to be extremely sensitive to a myriad of environmental factors, ranging from temperature to food levels (Zwaan et al, 1991(Zwaan et al, , 1992Carey et al, 2002). Furthermore, lifespan can also become severely curtailed upon inbreeding, as has already been demonstrated by Clarke and Maynard Smith (1955), who showed that hybrids between two inbred lines showed a large increase in lifespan.…”
Section: Introductionmentioning
confidence: 81%
“…The actual causes of gene-by-environment interactions remain unknown for most characters, but may reflect significant changes in the underlying physiology and genetic determination of the affected traits. Lifespan appears to be a suitable trait for the study of such interactions, since it is assumed to be extremely sensitive to a myriad of environmental factors, ranging from temperature to food levels (Zwaan et al, 1991(Zwaan et al, , 1992Carey et al, 2002). Furthermore, lifespan can also become severely curtailed upon inbreeding, as has already been demonstrated by Clarke and Maynard Smith (1955), who showed that hybrids between two inbred lines showed a large increase in lifespan.…”
Section: Introductionmentioning
confidence: 81%
“…When larval nutrition was limited in order to slow development and reduce adult body size, stature again was inversely associated with life span, at least among females. In further work, size was manipulated by rearing larvae at three temperatures while adult longevity was assessed in common thermal conditions (Zwaan et al, 1992). Among groups, larvae from the lowest temperature had the largest adult body size but the shortest life span.…”
Section: Discussionmentioning
confidence: 99%
“…This work has regularly included examinations of the proximate determinants of size variation French et al 1998;Azevedo et al 2002), and the effects of this variation on, for example, fecundity, longevity and developmental time (Zwaan et al 1992;James and Partridge 1995;McCabe and Partridge 1997;Bangham et al 2002).…”
Section: Introductionmentioning
confidence: 99%